Ablation of selected dental materials using Er,Cr:YSGG laser - Fatanah M.Suhaimi; Nur Hazeeqah Ahmad Pouzi; Nurulakma Zali; Nur Syazana Azizan; N. A. Abd Razak; M. K. A. A. Razab (Trans Tech Publications, 2017)
The effect of Er,Cr:YSGG laser for ablation of commercialized adhesive dental materials were studied using 12 sets of tooth samples. The surface morphology and composition of the tooth samples was observed before and after irradiation using FESEM and EDX. Time dependency of exposure is observed in the tooth sample. Adhesive material Grēngloo produced better ablation on long exposure compared to adhesive material Blūgloo. The ablation effect was also compared between presence and absence of water. The enamel surface produced is highly dependent on the technique used to ablate the adhesive material. Without water, enamel surface appeared roughed and depth of crater was also created. In particular, both materials produce different quality of ablation and reacted differently under different laser parameter and setting.